The “Holy Grail” of digital humanists: some thoughts about “understanding data” (for humanists) - Karcher, Stefan (DARIAH open, 2020)
As a reader of blog posts, you might be well aware how important role commentaries happening on blogs can play in the establishment of a specific scholarly discourses. In this piece, you can read our guest author's, Stefan Karcher's reflection on Jim Casey's recent blog post, Taste the Data where he introduces a new didactic approach to discover important information and structures in a data set. So, how do your data taste?